Hormone replacement therapy and colorectal cancer - Bednarowska-Flisiak, Alicja; Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2003)
Colorectal cancer is one of the leading causes of cancer deaths. The protective role of endogenous and exogenous estrogens in colon carcinogenesis is still under study. The analysis and meta-analysis of hormone replacement therapy (HRT) studies suggest a noticeable reduction in colon cancer among current and recent users. The 2002 results of randomized controlled study – Women’s Health Initiative confirm a 36% reduction of colorectal cancer in HRT users.